2022
DOI: 10.3390/rs14061389
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of BDS-3 Onboard Clocks Based on GFZ Precise Clock Products

Abstract: The characteristics and performance of satellite clocks are important to the positioning, navigation, and timing (PNT) services of Global Navigation Satellite System (GNSS) users. Although China’s BeiDou-3 Navigation Satellite System (BDS-3) has been fully operational for more than one year, there is still a lack of comprehensive research on the onboard clocks of the entire BDS-3 constellation. In this study, the precise clock products of GeoForschungsZentrum (GFZ) from day-of-year (DOY) 1, 2021 to DOY 300, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…It has been shown that BE-PPP with Galileo and the Global Positioning System (GPS) can provide a positioning accuracy of a few decimeters when post-processed products or real-time orbit and clock streams are not available (Carlin et al, 2021;Hadas et al, 2019). With the improved accuracy of the BDS-3 orbit and clock offset (Geng et al, 2022), BE-PPP for BDS has become feasible and offers better accuracy than standard point positioning (G. , but lower accuracy than traditional PPP (Hadas et al, 2019). Carlin et al (2021) conducted GPS/Galileo-integrated BE-PPP and estimated the signal-in-space range error (SISRE), which represents the projected orbit and clock errors introduced by the broadcast ephemeris, and obtained a significant improvement in positioning accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that BE-PPP with Galileo and the Global Positioning System (GPS) can provide a positioning accuracy of a few decimeters when post-processed products or real-time orbit and clock streams are not available (Carlin et al, 2021;Hadas et al, 2019). With the improved accuracy of the BDS-3 orbit and clock offset (Geng et al, 2022), BE-PPP for BDS has become feasible and offers better accuracy than standard point positioning (G. , but lower accuracy than traditional PPP (Hadas et al, 2019). Carlin et al (2021) conducted GPS/Galileo-integrated BE-PPP and estimated the signal-in-space range error (SISRE), which represents the projected orbit and clock errors introduced by the broadcast ephemeris, and obtained a significant improvement in positioning accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Kuang et al developed an uncombined model for the estimation of a BDS-3 multi-frequency real-time clock, and the STD of the double-differenced clock was generally less than 0.05 ns [17]. A series of research on the physical characteristics of atomic clocks show that the quality of BDS-3 atomic clocks is greatly improved compared with BDS-2, but the clock offset and frequency of BDS-3 still exist jumps, and the frequency drift varies in range from −2 × 10 −18 to 2 × 10 −18 s/s 2 [18]. About 70% of BDS-3 positioning solutions are within 0.7 m at 10 min thanks to the improvement in the BDS-3 atomic clock stability [19].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [11] analyzed the precise clock products for BDS-3 from GeoForschungsZentrum and showed the characteristics and performance in terms of clock bias, frequency, drift rate, fitting residuals, periodicity, and frequency stability.…”
mentioning
confidence: 99%